How do central banks talk? - Blinder, Alan S.; International Center for Monetary and Banking Studies; Centre for Economic Policy Research (Great Britain). (Geneva : International Center for Monetary and Banking Studies ; London : Centre for Economic Policy Research, 2001)
This report describes and evaluates some of the changes in how central banks talk to the markets, to the press, and to the public.
Includes bibliographical references (p. 119-122).
rua 31/08/16
Loans
Keywords: Banks and banking, Central